The thiol oxidation-based sensing and regulation mechanism for the OasR-mediated organic peroxide and antibiotic resistance in C. glutamicum. Issue 19 (5th October 2020) - Si, Meiru; Chen, Can; Che, Chengchuan; Liu, Yang; Li, Xiaona; Su, Tao
Abstract : Corynebacterium glutamicum, an important industrial and model microorganism, inevitably encountered stress environment during fermentative process. Therefore, the ability of C. glutamicum to withstand stress and maintain the cellular redox balance was vital for cell survival and enhancing fermentation efficiency. To robustly survive, C. glutamicum has been equipped with many types of redox sensors. Although cysteine oxidation-based peroxide-sensing regulators have been well described in C. glutamicum, redox sensors involving in multiple environmental stress response remained elusive. Here, we reported an organic peroxide- and antibiotic-sensing MarR (multiple antibiotics resistance regulators)-type regulator, called OasR (organic peroxide- and antibiotic-sensing regulator). The OasR regulator used Cys95 oxidation to sense oxidative stress to form S -mycothiolated monomer or inter-molecular disulfide-containing dimer, resulting in its dissociation from the target DNA promoter. Transcriptomics uncovered the strong up-regulation of many multidrug efflux pump genes and organic peroxide stress-involving genes in oasR mutant, consistent with the phenomenon that oasR mutant showed a reduction in sensitivity to antibiotic and organic peroxide. Importantly, the addition of stress-associated ligands such as cumene hydroperoxide and streptomycin induced oasR and multidrug efflux pump protein NCgl1020 expression in vivo . We speculated that cell resistance to antibiotics and organic peroxide correlated with stress response-induced up-regulation of genes expression. Together, the results revealed that OasR was a key MarR-type redox stress-responsive transcriptional repressor, and sensed oxidative stress generated through hydroxyl radical formation to mediate antibiotic resistance in C. glutamicum .